PEREMPUAN DAN SEKS : STUDI HADIS-HADIS TENTANG LAKNAT MALAIKAT TERHADAP ISTRI YANG MENOLAK AJAKAN SUAMI - Isti'anah, Isti'anah (El-Mu'Jam. Jurnal Kajian Al Qur'an dan Al-Hadis, 2022)
In married life, the husband should be able to position his wife as a balanced and equal partner. Not only as a complement to life and sexual satisfaction alone. A husband has the responsibility to help his wife's work, and vice versa, the wife must take part in helping to bear the burden of responsibility to relieve her husband. Husbands may not claim the right of "special services" regardless of the physical or psychological condition of the wife, on the pretext of the Prophet's hadith. From here, it is important to review the hadiths related to the curse of angels on wives who refuse husbands' invitations, to get a comprehensive meaning. This study uses a thematic method with a descriptive analysis approach to the texts of the Prophet's traditions relating to the intervention of angels in husband-wife sexual relations. That is by compiling hadiths related to the theme of the discussion, and tracing the asbab wurud, matan, and the hadith sanad.